Culture of tiger milk mushroom - Soniya Nair, Suresh (2025)
In this study, tiger milk mushrooms (Lignosus rhinocerus) cultivated on various media and nutrient sources are examined for their growth characteristics, bioactive qualities, and possible uses. The best medium was determined to be PDA agar because of its high carbon content, which offers ideal growth conditions. The biomass weight peaked after 10 days of incubation in MCM medium but then decreased because of resource depletion. Biomass development was efficiently stimulated by carbon sources such as lactose and glucose, but not by sucrose or Gula Melaka, perhaps because of impurities or phenolic chemicals. The nitrogen sources that promoted biomass growth were meat peptone, ammonium nitrate, and yeast extract; sodium nitrate had no impact. Its potential as a nutraceutical element was highlighted by the polyphenol analysis of the cultivated mushroom extract, which showed high amounts of total phenolic content (70.24±0.46mg/L), total caffeoylquinic acid (81.55±1.41mg/L), and total flavonoids (515±5.00mg/L). At the concentration of 20–40 mg/mL, antioxidant activity, as shown by IC₅₀ values, was effective but less than that of ascorbic acid. Compared to Gram-negative bacteria (Escherichia coli), the extract showed stronger suppression against Gram-positive bacteria (Bacillus subtilis). These results highlight the potential of tiger milk mushrooms as ingredients for functional foods because of their advantageous growth, and antibacterial, and antioxidant qualities.